The Application of the Teams Games Tournament (TGT) Method to Improve Students' Learning Interest in Indonesian Language Subject on Expository Text Material - Rohmatin, Amalia; Widigda, Aditya Nata; Afkar , Taswirul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Education plays a crucial role in shaping an intelligent and competitive nation, as through education, students can acquire the knowledge and skills necessary to face future challenges. One of the key factors supporting the success of education is the use of appropriate and engaging teaching methods, which can enhance students' learning interest and facilitate a deeper understanding of the subject matter. In this context, this research was conducted to increase the learning interest of eighth-grade students at MTS Bahrul Ulum by applying the Teams Games Tournament (TGT) method in Indonesian language learning, specifically in the Expository Text material. The TGT method was chosen because it creates an enjoyable and challenging learning environment, which in turn can encourage students to become more active in the learning process. This study was carried out in two cycles, with data collected through observation, interviews, and tests to evaluate the development of students' interest and understanding of the material being taught. Therefore, it is expected that the application of this method can improve the quality of teaching and students' learning outcomes optimally.